2022
DOI: 10.4256/ijmtl.v23i1.361
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Prospective Mathematics Teachers' Understanding of Derivative across Different Real-life Contexts

Abstract: This study investigates prospective secondary school mathematics teachers' developing conceptions about the meaning of derivative (as rate of change) while working on a series of tasks involving different non-motion real-life contexts. The study was conducted by employing a case study method. The participants of the study were 25 prospective secondary school mathematics teachers enrolled in the mathematics teaching methods course. A series of contextual tasks involving different real-life situations about deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…These misinterpretations portray the inconsistency of both participants regarding the occurrence of variables or quantities involved in rate of change within the situated context. This problem is similar to past studies (e.g., Byerley & Thompson, 2017;Kertil & Dede, 2022;Mkhatshwa & Doerr, 2018), where teachers and students often confused "amount" with "amount of change". In one study, a student named Brian interpreted rate of change as an amount of quantity rather than the changes between quantities.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These misinterpretations portray the inconsistency of both participants regarding the occurrence of variables or quantities involved in rate of change within the situated context. This problem is similar to past studies (e.g., Byerley & Thompson, 2017;Kertil & Dede, 2022;Mkhatshwa & Doerr, 2018), where teachers and students often confused "amount" with "amount of change". In one study, a student named Brian interpreted rate of change as an amount of quantity rather than the changes between quantities.…”
Section: Discussionsupporting
confidence: 69%
“…There is a lack of thorough research focusing on preservice mathematics teachers' knowledge of rate of change. Existing studies (e.g., Dane et al, 2016;Fothergill, 2011;Kertil, 2014;Kertil & Dede, 2022) among pre-service mathematics teachers primarily focus on broader calculus topics such as derivatives, limits, or integrals. These studies have consistently shown weak knowledge of derivatives conception and a lack of awareness of its connection to rate of change.…”
Section: / 18mentioning
confidence: 99%
See 1 more Smart Citation